A 2D DEM-LBM study on soil behaviour due to locally injected fluid - Cui, Xilin; Li, Jun; Chan, Andrew; Chapman, David (Particuology, 2012)
Leakage from underground pipes could result in foundations being undermined and cause damage to adjacent infrastructure. Soil particles surrounding the leaking area could be mobilised, displaced, and even washed out of the soil matrix by the leaking fluid, generating a void or cavity. A two-dimensional simulation using a coupled discrete element method and lattice Boltzmann method （DEM-LBM） has been used to investigate the behaviour of a soil bed subject to a locally injected fluid, which represents a leak in a pipe. Various values of inter-particle surface energy were also adopted to model the mechanical effects of cohesive particles. The results suggest that the inter-particle surface energy greatly influences the bed response with respect to the leaking fluid, including the excess pressure initiating the cavity, the cavity shape and its evolution rate.